Modifikasi Perilaku Aparatur Ala Skinner: Suatu Model Pengembangan Sumber Daya Manusia Menuju Profesionalisme Birokrasi - Dzakiyati, Fiki (Pusat Penelitian dan Pengabdian pada Masyarakat Sekolah Tinggi Ilmu Administrasi (STIA) Mataram, 2018)
The direction of policy reform bureaucracy is to increase the professionalism of the state apparatus and improvement of governance. In fact, bureaucracy in Indonesia have not yet been able to achieve the desired condition. Various phenomena which occurs as slow of public services and the bureaucracy that circular shows unprofessional attitude a bureaucracy. To change it, needed human resources management. Based on the theory of Skinner based on psychology behavioristik, Professionalism apparatus improvement can be done through behavior modification using operant conditioning load by providing stimulant in the form of rationalisation, formed a new bureaucracy culture, the improvement of the quality of human resources and supervision of the community.